Proletarianization of Professional Employees and Underemployment of General Intellect in a “Knowledge Economy”: Canada, 1982–2016 - Livingstone, D. W. (Labour / Le Travail, 2019)
Proletarianization refers to the subordination of hired labour to the owners of capital. This inquiry assesses the extent of proletarianization of professional employees on the basis of a distinctive series of national surveys of the general labour force in Canada between 1982 and 2016. Non-managerial professional employees are distinguished from professionals in other class positions (i.e. professional employers, self-employed professionals, and professional managers) with whom they have been conflated in much of the prior research. The findings suggest increasing proletarianization of professional employees during this period in terms of declining job autonomy and decreasing participation in organizational decision-making, as well as increasing underemployment and more critical political attitudes. But there is also evidence of increasing qualifications and development of “general intellect” among more traditional working-class employees, as well as even more extensive underemployment. Implications of convergence between the proletarianization of professional employees, as a “new working class,” and the qualifications and perceived working conditions of other non-managerial hired labour in emergent “knowledge economies” are discussed. More careful distinctions between non-managerial professional employees and professionals in other class positions in future studies are recommended.